2021
DOI: 10.3390/jmse9070763
|View full text |Cite
|
Sign up to set email alerts
|

Response to Environmental Factors of Spawning Ground in the Pearl River Estuary, China

Abstract: Spawning grounds are important areas for fish survival and reproduction, and play a key role in the supplement of fishery resources. This study investigated environmental effects on the spatiotemporal variability of spawning ground in the Pearl River Estuary (PRE), China, using the generalized additive model (GAM), based on satellite remote sensing (sea surface temperature (SST), chlorophyll-a concentration (Chl-a), sea surface salinity (SSS), depth), and in situ observations. Results showed that 39.8% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Investigations conducted in the lower PRE have shown that sea surface salinity is one of the crucial factors in explaining the variation in fish egg density in spawning grounds [62]. Hence, the findings of this study may hold valuable reference significance for analyzing and predicting the invasion of invasive fish species.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Investigations conducted in the lower PRE have shown that sea surface salinity is one of the crucial factors in explaining the variation in fish egg density in spawning grounds [62]. Hence, the findings of this study may hold valuable reference significance for analyzing and predicting the invasion of invasive fish species.…”
Section: Discussionmentioning
confidence: 64%
“…Tinca tinca , for example, has been found in tributaries but not yet in the PRD region, possibly due to its inability to adapt to the water environment in this area [61]. Investigations conducted in the lower PRE have shown that sea surface salinity is one of the crucial factors in explaining the variation in fish egg density in spawning grounds [62]. Hence, the findings of this study may hold valuable reference significance for analyzing and predicting the invasion of invasive fish species.…”
Section: Discussionmentioning
confidence: 99%
“…Tinca tinca, for example, has been found in tributaries but not yet in the PRD region, possibly due to its inability to adapt to the water environment in this area (Ding, 2020). Investigations conducted in the lower PRE have shown that sea surface salinity is one of the crucial factors in explaining the variation in sh egg density in spawning grounds (Wang et al, 2021). Hence, the ndings of this study may hold valuable reference signi cance for analyzing and predicting the invasion of invasive sh species.…”
Section: Discussionmentioning
confidence: 70%
“…Elemental concentrations in otolith cores can reflect spawning area environments (Mu et al, 2021), while the otolith edge can reflect the current habitat environment where the fish are caught. Spawning grounds are critical for fish survival and reproduction and play a key role in supplementing fishery resources (Wang et al, 2021). The difference analysis showed no significant differences between the otolith cores of the three sampling areas.…”
Section: Possibility Of Spawning Areas For a Latus In The Waters Of M...mentioning
confidence: 84%